Flavonoid Accumulation Plays an Important Role in the Rust Resistance of Malus Plant Leaves - Lu, Yanfen; Chen, Qi; Bu, Yufen; Luo, Rui; Hao, Suxiao; Zhang, Jie; Tian, Ji; Yao, Yuncong (Frontiers in Plant Science, 2017)
Cedar-apple rust (Gymnosporangium yamadai Miyabe) is a fungal disease that causes substantial injury to apple trees and results in fruit with reduced size and quality and a lower commercial value. The molecular mechanisms underlying the primary and secondary metabolic effects of rust spots on the leaves of Malus apple cultivars are poorly understood. Using HPLC, we found that the contents of flavonoid compounds, especially anthocyanin and catechin, were significantly increased in rust-infected symptomatic tissue (RIT). The expression levels of structural genes and MYB transcription factors related to flavonoid biosynthesis were one- to seven-fold higher in the RIT. Among these genes, CHS, DFR, ANS, FLS and MYB10 showed more than a 10-fold increase, suggesting that these genes were expressed at significantly higher levels in the RIT. Hormone concentration assays showed that the levels of abscisic acid (ABA), ethylene (ETH), jasmonate (JA) and salicylic acid (SA) were higher in the RIT and were consistent with the expression levels of McNCED, McACS, McLOX and McNPR1, respectively. Our study explored the complicated crosstalk of the signal transduction pathways of ABA, ETH, JA and SA; the primary metabolism of glucose, sucrose, fructose and sorbitol; and the secondary metabolism of flavonoids involved in the rust resistance of Malus crabapple leaves.